Review: Augustinus–Hieronymus. Epistulae Mutuae/Briefwechsel - Chadwick, Henry 1920-2008 (2003)
Augustinus–Hieronymus. Epistulae Mutuae/Briefwechsel 2 vols. Translated and introduced by Alfons Fürst Pp. 543 (numbered continuously) (Fontes Christiani, 41, 1 and 2.) Turnhout Brepols 2002 2 503 52101 0 52102 9 (vol. 1) 2 503 52103 7 52104 5 (vol. 2). Hardback n.p.; paper € 30.75 € 32.62
Keywords: Rezension